Regulation of GDF-15, a distant TGF-β superfamily member, in a mouse model of cerebral ischemia - Schindowski, Katharina; von Bohlen und Halbach, Oliver; Strelau, Jens; Ridder, Dirk; Herrmann, Oliver; Schober, Andreas; Schwaninger, Markus; Unsicker, Klaus (Cell & tissue research, 2011)
GDF-15 is a novel distant member of the TGF-β superfamily and is widely distributed in the brain and peripheral nervous system. We have previously reported that GDF-15 is a potent neurotrophic factor for lesioned dopaminergic neurons in the substantia nigra, and that GDF-15-deficient mice show progressive postnatal losses of motor and sensory neurons. We have now investigated the regulation of GDF-15 mRNA and immunoreactivity in the murine hippocampal formation and selected cortical areas following an ischemic lesion by occlusion of the middle cerebral artery (MCAO). MCAO prominently upregulates GDF-15 mRNA in the hippocampus and parietal cortex at 3 h and 24 h after lesion. GDF-15 immunoreactivity, which is hardly detectable in the unlesioned brain, is drastically upregulated in neurons identified by double-staining with NeuN. NeuN staining reveals that most, if not all, neurons in the granular layer of the dentate gyrus and pyramidal layers of the cornu ammonis become GDF-15-immunoreactive. Moderate induction of GDF-15 immunoreactivity has been observed in a small number of microglial cells identified by labeling with tomato lectin, whereas astroglial cells remain GDF-15-negative after MCAO. Comparative analysis of the size of the infarcted area after MCAO in GDF-15 wild-type and knockout mice has failed to reveal significant differences. Together, our data substantiate the notion that GDF-15 is prominently upregulated in the lesioned brain and might be involved in orchestrating post-lesional responses other than the trophic support of neurons.
Published online: 3 December 2010
Gesehen am 11.10.2022